Balancing climate change mitigation and national adaptation: Experimental evidence on the influence of risk perceptions and information construal levels - Jonas Heckenhahn; Christoph Feldhaus; Andreas Löschel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Climate change can be addressed by mitigation and adaptation approaches at the national policy level. Since only limited resources are available for both strategies, it is key to unravel how ongoing climate developments and their communication influence the population's preferences regarding the question 'adaptation or mitigation?' Based on construal level theory and the construal matching premise, we hypothesize that when individuals are faced with an abstract tradeoff between mitigation and national adaptation, a larger national short-term risk perception extends prioritization of national adaptation measures, whereas an amplified global long-term risk perception or a lifted construal level of presented climate risks increases mitigation emphasis. To explore these hypotheses, we conducted an online framed field information experiment with a German population sample of 2,182 participants and find evidence for the hypothesized causal effects by conducting OLS regressions and mediator analyses. We argue for reevaluating current climate communication's emphasis on psychologically close damages, as this approach may push people towards favoring adaptation strategies over essential mitigation measures and could thus entail undesirable side effects. – – Der Klimawandel kann auf nationalpolitischer Ebene durch Minderung und Anpassung angegangen werden. Da für beide Strategien nur begrenzte Ressourcen zur Verfügung stehen, ist es von zentraler Bedeutung, herauszufinden, wie die aktuellen klimatischen Entwicklungen und deren Kommunikation die Präferenzen der Bevölkerung hinsichtlich der Frage 'Anpassung oder Minderung?' beeinflussen. Basierend auf der Construal Level Theory und der Prämisse des Construal Matching hypothetisieren wir, dass, wenn Individuen mit einer abstrakten Abwägungsentscheidung zwischen Minderung und nationaler Anpassung konfrontiert sind, eine größere national-kurzfristige Risikowahrnehmung die Priorisierung nationaler Anpassungsmaßnahmen erhöht, während eine verstärkte global-langfristige Risikowahrnehmung oder ein erhöhtes Construal Level der dargestellten Klimarisiken den Fokus auf Minderung stärkt. Um diese Hypothesen zu untersuchen, haben wir ein Online Framed Field Information Experiment mit einer deutschen Bevölkerungsstichprobe von 2.182 Teilnehmern durchgeführt und basierend auf OLS-Regressionen und Mediatoranalysen Evidenz für die hypothetisierten kausalen Effekte gefunden. Wir plädieren dafür, die Betonung psychologisch naher Schäden in der aktuellen Klimakommunikation zu überdenken, da dieser Ansatz Menschen dazu verleiten könnte, Anpassungsstrategien gegenüber essenziellen Minderungsmaßnahmen zu bevorzugen, und somit unerwünschte Nebeneffekte nach sich ziehen könnte.
Keywords: Q54; D81; Q58; D91; C93; 330; Climate change mitigation; climate change adaptation; national adaptation strategies; psychological distance; construal level theory; risk perception; climate communication; information experiment